The theory of death : a Decker/Lazarus novel - Kellerman, Faye (New York, NY : William Morrow, an imprint of HarperCollinsPublishers, 2015)
Now living in upstate New York, former LAPD lieutenant Peter Decker is plunged into a bizarre web involving academia, underworld crime, and calculating killers.
Keywords: Decker, Peter -- (Fictitious character) -- Fiction; Lazarus, Rina -- (Fictitious character) -- Fiction; Ex-police officers -- Fiction; Murder -- Investigation -- Fiction; New York (State) -- Fiction; Detective and mystery fiction